2002
DOI: 10.3354/dao049011
|View full text |Cite
|
Sign up to set email alerts
|

Detection of white spot syndrome virus (WSSV) of shrimp by means of monoclonal antibodies (MAbs) specific to an envelope protein (28 kDa)

Abstract: The vp28 gene encoding an envelope protein (28 kDa) of white spot syndrome virus (WSSV) was amplified from WSSV-infected tiger shrimp that originated from Malaysia. Recombinant VP28 protein (r-28) was expressed in Escherichia coli and used as an antigen for preparation of monoclonal antibodies (MAbs). Three murine MAbs (6F6, 6H4 and 9C10) that were screened by r-28 antigen-based enzyme-linked immunosorbent assay (ELISA) were also able to recognize viral VP28 protein as well as r-28 on Western blot. Three non-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…Monoclonal antibodies against Vp28 of WSSV were prepared as described in Liu et al (2002). Briefly, spleen cells obtained from Balb/c mice that were immunized with 3 doses of purified recombinant Vp28 protein were fused with X63Ag8.653 mouse myeloma cells (ATCC) in the presence of PEG 1500.…”
Section: Methodsmentioning
confidence: 99%
“…Monoclonal antibodies against Vp28 of WSSV were prepared as described in Liu et al (2002). Briefly, spleen cells obtained from Balb/c mice that were immunized with 3 doses of purified recombinant Vp28 protein were fused with X63Ag8.653 mouse myeloma cells (ATCC) in the presence of PEG 1500.…”
Section: Methodsmentioning
confidence: 99%
“…In AmEPV-infected cells, spheroidin alone accounts for up to 30-40% of the total protein of infected insect cells (Winter et al 1995). WSSV also has several highly expressed structural genes/proteins, and, to date, the major structural protein VP28 has been the most commonly used WSSV target for immuno-based detection (Liu et al 2002, Yoganandhan et al 2004. Here, however, we have shown that the transcription expression levels of ICP11 are approximately 3 脳 greater than those of VP28.…”
Section: Discussionmentioning
confidence: 73%
“…The sensitivity of this kind of test depends on the immuno-detected target protein, and several candidate proteins have already been conside-Identification of icp11, the most highly expressed gene of shrimp white spot syndrome virus (WSSV) red. Liu et al (2002) and Yoganandhan et al (2004) independently developed procedures that targeted the WSSV major envelope protein, VP28, while Okumura et al (2005) developed a reverse passive latex agglutination method to detect WSSV virion particles by using anti-WSSV immunoglobulin G (IgG). All 3 of these studies were based on WSSV structural proteins, which until now were thought to be the most highly expressed proteins of WSSV.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been shown with WSSV that ELISA detection is substantially improved by using two complementary MAb that target different epitopes of a single viral coat protein. 21 A similar phage display approach might be applied for improvement of the similar detection strip for white spot syndrome virus (WSSV) of shrimp that uses a gold-labeled MAb specific to the 28 kDa envelope protein VP28 22 and a polyclonal antibody at the trap line. Results from dot-blot ELISA tests with all 13 YBPs (in two replicates) dotted on membranes.…”
Section: Biopanning For Yhv Binding Peptides Biopanning For Yhv Bindimentioning
confidence: 99%